Exploration of the Source-Impression Relationship in Warranting Theory: Other-Generated Content, Perceptions of Warranting Value, and Weight - Cherney, Maura (Human Communication & Technology, 2023)
Many early studies of warranting theory investigated the role of source, often self-generated and other-generated content, in the impression formation process but did not explicitly test perceptions of warranting value and sometimes were met with mixed results. The present study revisits the source-impression relationship and offers explicit tests of some of the assumptions of past warranting theory literature. An additional variable in the impression formation process, weight, is proposed as a potential explanation for past mixed results. The present study finds support for warranting theory in the impression students form of an instructor. Other-generated content has a greater impact on impressions and is higher in warranting value than self-generated content. The role of warranting value and the role of weight in the source-impression relationship is not supported. Implications for the general support of warranting theory but lack of support for clarifying variables are discussed.